Encouraging Productivity Chain Through Zakat Values - Sabila Rosyida; Syamsuri Syamsuri; Syamsyuddin Arif (AIBPM Publisher, 2019)
Zakat is a wealth transfer from the rich to the poor to improve the welfare of poverty. Further, zakat has broad implications and values to study. This paper aims to explore zakat values in encouraging the productivity chain. It uses a qualitative research approach with library research and unstructured interviews. The study found several interesting findings. First, zakat values are not only wealth transfer for consumptive purposes, but also encourage ummah to be productive and avoid consumerism. Second, the encouragement of productivity contains in zakat values is not only to maximize profits but also intended to maximize the maslahah. It also explains that zakat values have a close relationship with the ideal concept of the economy to achieving welfare.